Estimating Demand for Imported Food Categories in Iraq - Yaseen Abdullah, Yaser; Mostafa Mohammed, Rezgar (Journal of Economics and Administrative Sciences, 2023)
Iraq is highly dependent on international markets to provide food for its residents. As imported food prices are highly dependent on crude oil prices in global markets, any shock in oil prices will have an impact on food consumption in the country. As a result, it is essential to study the demand for imported food at every time period. To the best of our knowledge as researchers, as not even a single study is available in the literature, this paper is considered the first to study the demand for imported food groups in Iraq. Therefore, the main objective of this research is to estimate demand elasticities for several imported food categories in Iraq. This study uses an Almost Ideal Demand System model to analyze the demand for imported food in Iraq from 1980-2003 and 2003-2020. Data are collected from secondary resources. The main results show that some food categories become demand inelastic after they were demand elastic in the first period. In contrast, demand for some food groups become more price sensitive in the second period after it was less price sensitive in the first period. There are also changes in some food categories after they became luxuries in the second period. The findings of this study provide valuable insights into the changing dynamics of food import demand in Iraq and have policy implications by helping the decision-makers to invest more in the local production of some food groups.Paper type: Research paper